Teaching quality – student perspective - Lasić-Lazić, Jadranka (Array, 2010)
This paper presents research that examines the student’s view on teaching quality assessment surveys conducted by the University of Zagreb. Research was conducted by survey where students were asked to rank by importance teaching quality characteristics. Research also examined student’s opinions on importance and influence of teaching quality control surveys on improvement of teaching practice. Main aim of this research is to find out which teaching characteristics students perceive as most important so that teachers can primarily focus their effort to improve those teaching practices. Similar research was conducted in year 2007 so this research will also present comparation of results between two generations of students. This research will became basis for longitudinal research which will explore change in student perception of importance of teaching quality characteristics during 5 years of their faculty education.